Concise Review: The Role of Oxygen in Hematopoietic Stem Cell Physiology. Issue 9 (September 2015) - Jež, Mojca; Rožman, Primož; Ivanović, Zoran; Bas, Tuba
Abstract : Molecular dioxygen, O2, is an important element in cellular microenvironment in vivo, and often overlooked in standard in vitro and ex vivo cell culture systems. Molecular oxygen is the ultimate electron acceptor in oxidative cellular respiration, and also a signal that regulates cell fate through concentration gradients. Recent advances in physiology of oxygen and adult stem cell research have shown that apart from being important for oxidative phosphorylation, thus energy metabolism, oxygen is also important as a signaling molecule and an integral part of the stem cell niche. This review article covers the influence of physiologically relevant oxygen levels on adult stem cells through highlighting the research on the effect of oxygen concentration on hematopoietic stem cell maintenance, proliferation and differentiation. This is important particularly to understand the embryonic and adult stem cell biology and physiology. The new discoveries in this field will help to further improve current tissue engineering and clinical applications. In addition, understanding the relationship between oxygen and stemness is invaluable for the advanced treatments of neoplastic diseases. Authors believe that in the future, active and programmed dynamic of oxygen levels will be routinely used for the programmed in vitro and ex vivo expansion of different adult stem cell types and tissue regeneration purposes. J. Cell. Physiol. 230: 1999–2005, 2015. © 2015 Wiley Periodicals, Inc.